2022
DOI: 10.1155/2022/4283534
|View full text |Cite
|
Sign up to set email alerts
|

The ceRNA Crosstalk between mRNAs and lncRNAs in Diabetes Myocardial Infarction

Abstract: Competitive endogenous RNA regulation suggests an intricate network of all transcriptional RNAs that have the function of repressing miRNA function and regulating mRNA expression. Today, the specific ceRNA regulatory mechanisms of lncRNA–miRNA–mRNA in patients who have diabetes mellitus (DM) and myocardial infarction (MI) are still unknown. Two data sets, GSE34198 and GSE112690, were rooted in the Gene Expression Omnibus database to search for changes of lncRNA, miRNA, and mRNA in MI patients with diabetes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…These noncoding RNAs might cause a decrease in miRNA after immune challenge. One competing endogenous RNA (ceRNA) regulatory system with three lncRNAs, two miRNAs, and nine mRNAs was constructed in diabetic cardiovascular diseases [ 65 ]. Another study identified a regulatory mechanism in which lncRNA-CR11538 interacts with transcription factors Dif/dorsal to suppress antimicrobial peptide expression and restore Drosophila Toll immune homeostasis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…These noncoding RNAs might cause a decrease in miRNA after immune challenge. One competing endogenous RNA (ceRNA) regulatory system with three lncRNAs, two miRNAs, and nine mRNAs was constructed in diabetic cardiovascular diseases [ 65 ]. Another study identified a regulatory mechanism in which lncRNA-CR11538 interacts with transcription factors Dif/dorsal to suppress antimicrobial peptide expression and restore Drosophila Toll immune homeostasis [ 66 ].…”
Section: Discussionmentioning
confidence: 99%